Metal Concentrations in Grape Spirits - van Wyk, T. N.; van Jaarsveld, F.; Caleb, O. J. (South African Journal of Enology and Viticulture, 2021)
Metals are a necessity for human health as they play significant roles in biological systems. However, contamination of food and beverages by heavy metals such as lead (Pb), iron (Fe), chromium (Cr), cadmium (Cd), copper (Cu), cobalt (Co), Nickel (Ni) and zinc (Zn) is a major public health problem in developing countries. In this study we evaluated the levels of Li, Be, B, Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Sr, Mo, Cd, Sb, Ba, Hg and Pb in grape spirits, including pot still spirit, neutral wine spirit and commercial brandies. Interesting variations in the levels of metals was observed. Factors such as origin and type of spirits influenced levels of metals in spirits. These differences in some metal levels such as copper can be used to determine possible adulteration and in authenticity assessments of brandies. Surprisingly the commercial brandies had higher metal concentrations when compared to pot still spirit and neutral wine spirit. Unmatured pot still spirit had the highest copper levels. Our study shows that generally the metal levels in most of the commercial brandies were within permissible limits.